Students’ Speaking Problem at the Fourth Semester of English Study Program in Sembilanbelas November Kolaka - Andas, Netty Huzniati (Universitas Negeri Makassar, 2020)
ABSTRACTThe objectives of this research were to find out the students’ speaking problemsat the fourth semester of English Study Program in Sembilanbelas November University and factors affecting them. This research employed case study with qualitative approach. There were 26 participants at class A of the fourth semester in English Study Program. Those participants were selected through purposive sampling technique. To gain the data interview, observation sheet, and students’ transcript report were used. The result showed that there were four problems that were experienced by students at the class A fourth semester first was inhibition, when speaking the students tend to be worried about making mistake, getting criticism from others, and shyness. The second was lack of ideas; the students tend to be silent participants in speaking due to lack of vocabulary and grammar. The third was low or uneven participation in speaking. Here, only few students participate the speaking activities while other remaining silent. And the last was students got difficulty to speak because of the influencing of mother-tongue use. There were two factors affecting the students’ speaking ability such as internal and external factors. The internal factors here the students have low motivation in speaking while the external factors were the students’ condition in the classroom